The United States' European Phased Adaptive Approach Missile Defense System Defending Against Iranian Missile Threats Without Diluting the Russian Deterrent - Sankaran, Jaganath (RAND Corporation, 2015)
In 2013, the United States opted to cancel Phase 4 of its European Phased Adaptive Approach missile defense system. Russia had cited it as a threat to its nuclear deterrent. This report demonstrates that the restructured U.S. system is able to defend against a range of current and future Iranian missile threats and does not pose a threat to Russian intercontinental ballistic missiles.